Tempus structural joint European project. Education for information management in Lithuania - Glasienė, Audronė; Gudauskas, Renaldas (Information & Media, 1996)
From the 1st of September 1995, the Faculty of Communication, University of Vilnius (FC) with other partners is involved in a three-year TEMPUS (PHARE) Structural Joint European Project (SJEP) Education for Information Management in Lithuania. This article aims to present the main ideas, goals, tasks and activities of the project. The main objective of the SJEP is to create and realize education framework for information management of integrated use of integrated information resources. Project has two major goals: • to create and realize postgraduate (magisterial) program for Information Management in Lithuania. Information Management is concerned with the planning, implementing/organising and controlling of information resources - these are: information contents, information systems and the information infrastructure. The goal of this Information Management program should be to train information professionals who are qualified to establish, manage, operate and evaluate user-oriented information systems and services, to coordinate available internal and external information flows in order to facilitate both work and decision-making processes in the organisations. Specialists of new type should be able to integrate the resources both of the computer centre and the library in the University information provision. Up to now computer centres and the libraries have resisted the view that information is a single conceptual entity that, for reasons of efficiency and effectiveness, needs to be managed as single resource at certain level. • to promote the creation of such information structure as Integrated Information Centre as the means for integrated use of computer centre and library resources at the university. Integrated Information Centre is an organisational entity whose mission is to provide informational and technical support services to the faculty and staff of an academic unit. Our partners in this project are four universities in Western European countries and two libraries in Lithuania: • Faculty of Communication, University of Vilnius, Coordinator dr. Renaldas Gudauskas • Fachhochschule Hannover (Germany), Contractor Prof. Dr.-Ing. Peter Blumendorf • University of North London (Great Britain), Contact Person Mr. Anthony Beard • Rijkshogeschool IJsselland (Netherlands), Contact Person Drs. Adriaan Borggreve • Stockholm University Library (Sweden), Contact Person Lennart Eklind • Vilnius Academy of Arts Library, Contact Person Ms. Dalia Šimienė • Martynas Mažvydas National Library of Lithuania, Contact Person Mr. Vladas Bulavas. Duration of the project - 3 years. Total grant - 367 thousand ECU.